A Pilot Study of Emotion Regulation Strategies Training: Enhancing Mothers' Understanding in Low-SES Families - Sulfani Nur Mawaddah; Rose Mini Agoes Salim (Universitas Ahmad Dahlan, 2026)
This pilot study evaluated preliminary changes in mothers’ understanding of emotion regulation strategies following an experiential learning-based training programme among low-SES families in a rural setting. Participants were 19 mothers of children aged four to six years from a rural village in Purwakarta, West Java, Indonesia. A one-group pretest–post-test design with a two-week follow-up assessment was employed. The training programme consisted of three sessions based on Gross and Ford’s process model of emotion regulation, covering situation selection, situation modification, attentional deployment, cognitive change, and response modulation. The sessions were delivered using Kolb’s experiential learning approach through role play, group discussion, contextual exercises, and interactive lectures. Mothers’ understanding was assessed at pretest, immediate post-test, and two-week follow-up using a researcher-developed instrument. The Friedman test showed a significant increase in understanding from pretest to immediate post-test, indicating a positive short-term change. However, this improvement was not statistically sustained at the two-week follow-up. These findings suggest that experiential learning-based emotion regulation training may offer preliminary benefits for strengthening mothers’ understanding of emotion regulation strategies. Nevertheless, given the small sample size and absence of a control group, the results should be interpreted cautiously. Future studies should employ controlled designs, larger samples, validated measures, and booster sessions to support the maintenance of training effects over time.